A literature review on cell formation problem in a batch oriented production system - Sarojit Kumar Biswas, Rubayet Karim, (International Journal of Scientific Research and Management (IJSRM), 2015)
One of the fundamental problems in cellular manufacturing system is the formation of part families and machine cells that is thecell formation. For cell formation the part families are identified that require similar processing on a set of machines. In turn,these machines are grouped into cells. Each cell is capable of satisfying all the requirements of the part family assigned to it.This paper address the major works in the field of machine part cell formation problem in a batch oriented production system.More specifically this paper discusses about different methods, models and algorithms developed for finding the solution for theprimary problem of design of manufacturing cells.